Characterization of a novel HLA‐C allele, HLA‐C*04:288, in an Italian patient. (1st June 2018) - Biagini, C.; Fornaciari, S.; Mariotti, M. L.; Scatena, F.; Curcio, M.
Abstract : The novel HLA‐C*04:288 differs from HLA‐C*04:01:01:06 by a single nucleotide substitution in exon 2.